PENGEMBANGAN APLIKASI ASURANSI SWASTA DENGAN METODE FOCUS PDCA DI RSUP SANGLAH DENPASAR - Astiarini Arifin; Atma Deharja; Ervina Rahmawati (Politeknik Negeri Jember, 2021)
The E-Pasti especially in the insurance department does not have a notification to the patient thatthe file for insurance has been processed. This resulted in patients having to call or come directlyto the hospital so that which becomes inefficient. This is caused by the absence of notification inthe poly system that the blank has been completed. The research method used in this research isto use the FOCUS PDCA method. The results obtained after carrying out the improvement phase,namely the Asuransu Submission Service, become more efficient because the patient no longerneeds to come or call the hospital to ask the status of the file.